Determinants and barriers of prehospital emergency medical services utilization among general critical emergency patients in Thailand - Songsak Poomsaidorn; Kittipong Sornlom; Wongsa Laohasiriwong; Roshan Kumar Mahato; Nikom Thanomsieng; Chatree Charoencheewakul (Intelektual Pustaka Media Utama, 2023)
This cross-sectional study identified the determinants and barriers of pre- hospital emergency medical services (EMS) utilization among general critical emergency patients in Thailand, using the data of general critical emergency patients (red zone) from the information technology for emergency medical system (ITEMS) of the National Emergency Medical Service Institute. The sample of 889 critical emergency patients was selected through multistage random sampling method. Data were analyzed by multiple logistic regression. The findings indicated that 41.51% of general critical emergency patients used EMS through the EMS rescue hotline system of the National Institute of Emergency Medicine in which most of them were diabetic patients (24.75%). The determinants relating to EMS utilization of general critical emergency patients consisted of level of knowledge on EMS system (AdjOR: 5.77; 95%CI: 2.8-11.87), confidence in the safety of service utilization (AdjOR: 5.04; 95%CI: 3.65-6.98), recognition in service and severity of illness (AdjOR: 3.22; 95%CI: 2.17-4.76), service adequacy (AdjOR: 1.92; 95%CI: 1.41-2.63), educational background (AdjOR:1.69; 95%CI: 1.13-2.53), and service satisfaction (AdjOR: 1.14; 95%CI: 1.07-1.21). Nearly half of the people were utilizing the EMS services in Thailand. However, required level of knowledge on EMS, confidence on safety on service utilization, service adequacy as well as patient’s educational background had tremendous role on the proper utilization of EMS.